2018
DOI: 10.1038/s41598-018-33383-1
|View full text |Cite
|
Sign up to set email alerts
|

The Duality of the MAPK Signaling Pathway in the Control of Metabolic Processes and Cellulase Production in Trichoderma reesei

Abstract: In this study, through global transcriptional analysis by RNA-Sequencing, we identified the main changes in gene expression that occurred in two functional mutants of the MAPK genes tmk1 and tmk2 in Trichoderma reesei during sugarcane bagasse degradation. We found that the proteins encoded by these genes regulated independent processes, sometimes in a cross-talk manner, to modulate gene expression in T. reesei. In the Δtmk2 strain, growth in sugarcane bagasse modulated the expression of genes involved in carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 97 publications
1
23
0
1
Order By: Relevance
“…Mitogen-activated protein kinase pathways are conserved signalling cascades in eukaryotes that are involved in the transduction of extracellular or environmental stimuli for transcriptional regulation [ 51 , 52 ]. In fungi, MAPK signalling pathways have been implicated to be involved in a wide range of processes such as fungal pathogenicity, mating, morphogenesis, stress resistance and cell wall integrity [ 53 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-activated protein kinase pathways are conserved signalling cascades in eukaryotes that are involved in the transduction of extracellular or environmental stimuli for transcriptional regulation [ 51 , 52 ]. In fungi, MAPK signalling pathways have been implicated to be involved in a wide range of processes such as fungal pathogenicity, mating, morphogenesis, stress resistance and cell wall integrity [ 53 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results from transcriptome sequencing (RNA-seq) analysis of T. reesei strains lacking the tmk2 MAPK grown on sugarcane baggase revealed that genes involved in G-protein-related processes are differentially regulated in this background. Among these are the T. reesei GNA-1 homolog as well as three Pth11-like GPCRs and an RGS gene ( 50 ), directly tying G-protein signaling to this MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The strain was maintained at 4 °C on MEX medium [malt extract 3% (w/v) and agar–agar 2% (w/v)], which was supplemented with 5 mM uridine in the case of the pyr4 deletion strain. For all experiments, a spore suspension of QM6aΔ tmus53 Δ pyr4 strain containing 10 6 cells/mL was precultured into 200 mL of Mandels–Andreotti medium [31] supplemented with glycerol 1% (w/v) for 24 h and then transferred to a 200 mL of fresh Mandels–Andreotti medium containing 1% of Avicel [32, 33]. The cultures were incubated on an orbital shaker (200 rpm) at 30 °C for 24, 48, 72, 96 or 120 h. For glucose experiments, the fungus was grown in 2% glucose for 24 h. The resulting culture supernatant was collected by filtration and used for EVs isolation.…”
Section: Methodsmentioning
confidence: 99%